If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3x + 5 = 117 Reorder the terms: 5 + X + 3x = 117 Solving 5 + X + 3x = 117 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + X + -5 + 3x = 117 + -5 Reorder the terms: 5 + -5 + X + 3x = 117 + -5 Combine like terms: 5 + -5 = 0 0 + X + 3x = 117 + -5 X + 3x = 117 + -5 Combine like terms: 117 + -5 = 112 X + 3x = 112 Add '-3x' to each side of the equation. X + 3x + -3x = 112 + -3x Combine like terms: 3x + -3x = 0 X + 0 = 112 + -3x X = 112 + -3x Simplifying X = 112 + -3x
| 18x+1=5x+2 | | 5(b-9)=12 | | x^2+6x+9+16=x^2+10x+25 | | 7x=5-4(1-3x) | | (x+3)2+16=(x+5)2 | | 4e+7-7=19-7 | | (7v+35)(v^2+7v+10)=0 | | b-3-2=9-2 | | 4a*5=8*5 | | 5x^2+20= | | 16t^2+108t+160=0 | | 5v^4-20v^3+25v^2=0 | | x(x-1)(1-x)= | | 5x+4x-3x=17+7 | | 9w^3+12w^2-21w=0 | | 9(3x-1)=4x-5x | | 4y^4-32y^3+64y^2=0 | | 9y^5-42y^4+24y^3=0 | | 7y^7-42y^6+63y^5=0 | | Sin(cosx)=cos(sinx) | | 3(n+1)-8(2-n)=20 | | 2+3x-1=6 | | X+.25=40 | | 5x+x=6x | | x^2-23x+30=0 | | 10=4(z-8)-6 | | P=50-0.2Q | | 12y-28=64 | | -2y-3(3z-6y)-4z= | | 5+2(4-7)= | | 6ab-2a+3ab+7b= | | 45-6y=63 |